2013
DOI: 10.1080/15325024.2012.719335
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies Used by School Staff After a Crisis: A Research Note

Abstract: There is much literature on crisis support in schools but little on how school staff are affected. This research had two aims: to begin to explore the coping strategies used by school staff after a crisis event, and to investigate measures that might prove valuable for future research. Seven cases are presented using three measures: the WHO (Five) Wellbeing Index, the Impact of Event Scale–Revised, and the Ways of Coping–Revised. Results from this initial study show great variation in the range of responses re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We made the modification to expand the inquiry to over six months in order to avoid any biases associated with transient and rotation-related stresses. According to a systematic review, the WHO-5 has been used to analyze a wide variety of aspects [1], including coping strategies [5], well-being in occupational health settings [6], the association between workplace stress and well-being [7], the links between working condition and well-being [8], as well as the association between psycho-social conditions and well-being [9]. We hypothesized that the stress level and the resulting negative impact on well-being will be the lowest in the early formative years, i.e., medical school and early residency, and will increase as one is further along in their training and career.…”
Section: Discussionmentioning
confidence: 99%
“…We made the modification to expand the inquiry to over six months in order to avoid any biases associated with transient and rotation-related stresses. According to a systematic review, the WHO-5 has been used to analyze a wide variety of aspects [1], including coping strategies [5], well-being in occupational health settings [6], the association between workplace stress and well-being [7], the links between working condition and well-being [8], as well as the association between psycho-social conditions and well-being [9]. We hypothesized that the stress level and the resulting negative impact on well-being will be the lowest in the early formative years, i.e., medical school and early residency, and will increase as one is further along in their training and career.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of stress research, the WHO-5 has been used to assess a wide variety of aspects including coping strategies [50], well-being in occupational health settings [51], the association between workplace stress and well-being [52], the links between working condition and well-being [53] as well as the association between psychosocial conditions and well-being [54]. In the study by Gao et al [52], it was found that approximately 35% of a total of 2,796 employees had low well-being (cut-off score on the WHO-5 of <50) and that low social capital at the workplace was associated with poor well-being.…”
Section: Resultsmentioning
confidence: 99%
“…The specific coping strategies individuals draw upon in an effort to resolve the stressor set the stage for longer term adjustment. Broadly speaking, adaptive strategies such as relaxation, good nutrition, and regular exercise reduce stress and promote long-term wellbeing and positive affect, whereas maladaptive strategies such as drug use, alcohol use, or interpersonal withdrawal erode long-term well-being (Cole et al, 2013;Everly & Lating, 2002). In relation to the pandemic in particular, there is growing evidence about the usefulness of engaging in the more positive and adaptive strategies.…”
Section: Forms Of Copingmentioning
confidence: 99%